2022
DOI: 10.1002/slct.202104584
|View full text |Cite
|
Sign up to set email alerts
|

A New Boron 2‐(2′‐pyridyl) Imidazole Complex as a Candidate Photosensitizer for Photodynamic Therapy

Abstract: In this work, different from the literature, boron 2-(2'-pyridyl) imidazole complex (BOPIM) was derived from pyridine ring side to extend π conjugation for the first time. In addition, the core of BOPIM was brominated to increase the capacity of singlet oxygen generation via intersystem crossing to function as a photosensitizer. According to photophysical measurements, the new BOPIM derivative had comparatively large Stokes shift as 111 nm among boron-fluorine derivatives in the literature. Its singlet oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The results showed that the pyrazole-containing porphyrin and chlorine compounds exhibited high aPDT activity against planktonic and biofilm forms of E. coli [ 13 ]. In the present study, a 2-(2′-pyridyl) imidazole (BOPIM) core, as one of the new photosensitizers in the literature [ 14 , 15 ], was used. The BOPIM structure, which has advantageous properties such as high Stokes shift, high quantum yield, fluorescence properties in solid state, and solubility in many solvents, was derivatized with 1-methyl pyrazole, which could have an antifungal effect.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the pyrazole-containing porphyrin and chlorine compounds exhibited high aPDT activity against planktonic and biofilm forms of E. coli [ 13 ]. In the present study, a 2-(2′-pyridyl) imidazole (BOPIM) core, as one of the new photosensitizers in the literature [ 14 , 15 ], was used. The BOPIM structure, which has advantageous properties such as high Stokes shift, high quantum yield, fluorescence properties in solid state, and solubility in many solvents, was derivatized with 1-methyl pyrazole, which could have an antifungal effect.…”
Section: Introductionmentioning
confidence: 99%